Mobile Learning-Based Clinical Education Management Information System (Cemis) And Its Effectiveness In Impro - Miming Oxyandi; Santhna Letchmi Panduragan; Faridah Mohd Said; Aris Citra Wisuda; Rhipiduri Rivanica (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
The quality of clinical Education is greatly influenced by students' success in clinical practice areas in achieving learning outcomes, most of which are still conventional and not yet integrated. This study aims to evaluate the effectiveness of mobile learning as a medium to assess clinical learning in nursing students. This study uses Randomized Controlled Trial design. Place and Duration of Study in IKesT Muhammadiyah Palembang. From Sept 2022 to May 2023. The sample for this research consisted of nursing students from Group Experimental (n=40) and control group (n=40). The types of analysis used were the Wilcoxon Sign Rank Test and N-Gain Score Test. The use of mobile learning-based CEMIS is proven to be significant and effective in improving the learning outcomes of clinical learning of nursing students with the results of the Wilcoxon Sign Rank Test in the experimental group and the control group, namely cognitive ability (Sysmp Sig 0.002 vs 0.057), Ability Psychomotor (Sysmp Sig 0.002 VS 0.057), ability Affective (Sysmp Sig 0.002 VS 0.057). Whereas the results of the N-Gain Score Test show ability cognitive 80% (Effective), ability Psychomotor 78% (Effective), ability Affective 78% (Effective). CEMIS-based nursing clinical learning has been proven effective in improving student learning outcomes, making it a potential alternative to support clinical. learning in nursing education.